2002
DOI: 10.1067/mva.2002.124373
|View full text |Cite
|
Sign up to set email alerts
|

Gamma radiation induces positive vascular remodeling after balloon angioplasty: A prospective, randomized intravascular ultrasound scan study

Abstract: This randomized IVUS study showed that gamma-radiation after PTA has a positive effect on lumen dimensions at 6-month follow-up by inducing positive vascular remodeling (ie, vascular dilatation); gamma-radiation seemed not to affect plaque growth. In addition, gamma-radiation has an effect on the healing process of dissections after PTA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Gamma radiation has induced positive vascular remodeling after balloon angioplasty in a prospective randomized intravascular ultrasound (IVUS) scan study. 23 When doses of 12-14 Gy (gamma radiation) are applied endoluminally to the femoropopliteal segment after PTA, there is a two-fold increase in 12-month patency compared to untreated controls. [24][25][26] Similar results were noted in the PARIS trial.…”
Section: Brachytherapy Balloonsmentioning
confidence: 99%
“…Gamma radiation has induced positive vascular remodeling after balloon angioplasty in a prospective randomized intravascular ultrasound (IVUS) scan study. 23 When doses of 12-14 Gy (gamma radiation) are applied endoluminally to the femoropopliteal segment after PTA, there is a two-fold increase in 12-month patency compared to untreated controls. [24][25][26] Similar results were noted in the PARIS trial.…”
Section: Brachytherapy Balloonsmentioning
confidence: 99%
“…28 Persistent dissection in patients with femoropopliteal obstructive disease treated with PTA plus EVBT has been also described with the use of serial intravascular ultrasound (IVUS). 29 Using noninvasive imaging, we definitively demonstrate that IVUS-detected persistent dissection 29 was not a result of catheter manipulation during the IVUS procedure but was most probably the result of delayed vessel healing after brachytherapy. In addition, by imaging the lesions before the catheter intervention, we demonstrate that in the short term there was no difference in the treatment between the groups, reducing a potential selection bias.…”
Section: Wyttenbach Et Almentioning
confidence: 99%
“…Forty RCTs were accepted into the narrative review, published in 61 references. Study characteristics are shown in Table S1 (supporting information). Most of the trials recruited participants who had angioplasty of the superficial femoral and/or popliteal artery.…”
Section: Resultsmentioning
confidence: 99%